Concise Total Synthesis of (+)-Aphanorphine - Wang, Cheng; Guan, Yukun (Synlett, 2021)
A concise total synthesis of (+)-aphanorphine is described. The key features of the strategy include a Pd-catalyzed intermolecular trimethylenemethane [3+2]-cycloaddition to form ring C and a Co-catalyzed radical cyclization through a hydrogen-atom transfer to close ring B. The synthesis was completed in six steps.
Keywords: aphanorphine; total synthesis; alkaloids; tert-butanesulfinimine; cycloaddition; hydrogen-atom transfer